Red man syndrome: an unusual complication of vancomycin beads (Bangladesh Journal of Medical Science, 2015)
Vancomycin is a bactericidal antibiotic. It is commonly used to treat Methicillin Resistant Staphylococcus Aureus (MRSA) infections. It is also used locally with Polymethyl methacrylate to treat chronic bone infections. Locally placed beads deliver high concentration of antibiotics locally with few adverse effects as compared to parenteral therapy. There are two complications mentioned on intravenous infusion of vancomycin namely anaphylactic reaction and red man syndrome; but there is no known literature on complications arising from vancomycin impregnated cement beads. We report a case of red man syndrome following usage of vancomycin impregnated cement beads which is not reported in any available orthopaedic literature.Bangladesh Journal of Medical Science Vol.14(3) 2015 p.290-291